The impact of intergenerational support on social participation patterns of older adults in rural China - Wang, Ping; Cheng, Xin (Frontiers in Public Health, 2024)
Objectives This study aimed to examine the association between and different dimensions of bi-directional intergenerational support on the social participation patterns of rural older adults, while also exploring the heterogeneity of older adults by gender and age. Methods Based on longitudinal survey data from the ‘Well-Being of Older People in Anhui Province (WESAP)’ in 2018 and 2021, this study used latent class analysis to identify social participation patterns and used multinomial logistic regressions to explore the relationship between intergenerational support and social participation patterns among rural older adults. Results First, the social participation patterns of rural older persons can be divided into four categories: leisure type (9%), work type (11%), housekeeping type (57.9%) and family labor type (22.1%). Second, there is heterogeneity in the relationship between intergenerational support and social participation patterns in older people, among them, receiving financial support decreased the likelihood of older adults being categorized as work type and family labor type by 14% and 7.7%, respectively, while providing financial support increased the likelihood of older adults belonging to the family labor type by 7.5%; receiving caring support increased the likelihood of older parents being categorized as leisure type by 6%, while providing caring support decreased the likelihood of older parents being categorized as leisure type by 10%; emotional support is related to all patterns of social participation among older adults. Third, the effects of intergenerational support vary across subgroups based on gender and age. Conclusion Two-way intergenerational support was significantly associated with social participation among rural older adults, and there was significant heterogeneity in this association. Children and older persons should be encouraged to strengthen two-way intergenerational mobility to give full play to the positive impact of different dimensions of intergenerational support on the social participation of older persons in rural areas, ultimately enhancing the quality of life for rural older adults.